Large-Scale Chromosomal Changes Lead to Genome-Level Expression Alterations, Environmental Adaptation, and Speciation in the Gayal (Bos frontalis). (10th January 2023) - Li, Yan; Wang, Sheng; Zhang, Zhe; Luo, Jing; Lin, Guo Liang; Deng, Wei-Dong; Guo, Zhifan; Han, Feng Ming; Wang, Li-Li; Li, Jie; Wu, Shi-Fang; Liu, He-Qun; et al.
Abstract: Determining the functional consequences of karyotypic changes is invariably challenging because evolution tends to obscure many of its own footprints, such as accumulated mutations, recombination events, and demographic perturbations. Here, we describe the assembly of a chromosome-level reference genome of the gayal ( Bos frontalis ) thereby revealing the structure, at base-pair-level resolution, of a telo/acrocentric-to-telo/acrocentric Robertsonian translocation (2;28) (T/A-to-T/A rob[2;28]). The absence of any reduction in the recombination rate or genetic introgression within the fusion region of gayal served to challenge the long-standing view of a role for fusion-induced meiotic dysfunction in speciation. The disproportionate increase noted in the distant interactions across pro-chr2 and pro-chr28, and the change in open-chromatin accessibility following rob(2;28), may, however, have led to the various gene expression irregularities observed in the gayal. Indeed, we found that many muscle-related genes, located synthetically on pro-chr2 and pro-chr28, exhibited significant changes in expression. This, combined with genome-scale structural variants and expression alterations in genes involved in myofibril composition, may have driven the rapid sarcomere adaptation of gayal to its rugged mountain habitat. Our findings not only suggest that large-scale chromosomal changes can lead to alterations in genome-level expression, thereby promoting both adaptation and speciation, but also illuminate novel avenues for studying the relationship between karyotype evolution and speciation.